Prkar1a gene knockout in the pancreas leads to neuroendocrine tumorigenesis. Issue 1 (January 2017) - Saloustros, Emmanouil; Salpea, Paraskevi; Starost, Matthew; Liu, Sissi; Faucz, Fabio R; London, Edra; Szarek, Eva; Song, Woo-Jin; Hussain, Mehboob; Stratakis, Constantine A
Abstract : Carney complex (CNC) is a rare disease associated with multiple neoplasias, including a predisposition to pancreatic tumors; it is caused most frequently by the inactivation of the PRKAR1A gene, a regulator of the cyclic AMP (cAMP)-dependent kinase (PKA). The method used was to create null alleles of prkar1a in mouse cells expressing pdx1 (Δ- Prkar1a ). We found that these mice developed endocrine or mixed endocrine/acinar cell carcinomas with 100% penetrance by the age of 4–5 months. Malignant behavior of the tumors was seen as evidenced by stromal invasion and metastasis to locoregional lymph nodes. Histologically, most tumors exhibited an organoid pattern as seen in the islet-cell tumors. Biochemically, the lesions exhibited high PKA activity, as one would expect from deleting prkar1a . The primary neuroendocrine nature of these tumor cells was confirmed by immunohistochemical staining and electron microscopy, the latter revealing the characteristic granules. Although the Δ- Prkar1a mice developed hypoglycemia after overnight fasting, insulin and glucagon levels in the plasma were normal. Negative immunohistochemical staining for the most commonly produced peptides (insulin, c-peptide, glucagon, gastrin and somatostatin) suggested that these tumors were non-functioning. We hypothesize that the recently identified multipotent pdx1+/insulin− cell in adult pancreas, gives rise to endocrine or mixed endocrine/acinar pancreatic malignancies with complete prkar1a deficiency. In conclusion, this mouse model supports the role of prkar1a as a tumor suppressor gene in the pancreas and points to the PKA pathway as a possible therapeutic target for these lesions.